Magnetic property of Fe2O3 and Fe3O4 nanoparticle prepared by solvothermal process. (2022) - Sahadevan, Jhelai; Sojiya, R.; Padmanathan, N.; Kulathuraan, K.; Shalini, M.G.; Sivaprakash, P.; Esakki Muthu, S.
Abstract: Maghemite and magnetite have attracted much attention in biomedical applications due to their low toxicity and biocompatibility in human body. Here we report the synthesis, structural, morphological and magnetic property of Fe2 O3 and Fe3 O4 nanoparticles. The Fe2 O3 and Fe3 O4 were synthesized by solvothermal method with the ethylene glycol and diethylene glycol respectively. Ferric nitrate was exclusively used to prepare Fe2 O3 and Fe3 O4 nanomaterials. Ethylene glycol and diethylene glycol act as reducing agent and limits the agglomeration. The obtained powders are characterized by X-ray diffractometry, scanning Electron microscopy (SEM) and Vibrating Sample magnetometer (VSM). The resulting Fe3 O4 particles have cubic structure and an average size of 15.16 nm. Similarly alpha Fe2 O3 had rhombohedral structure with average size of 31.22 nm. VSM analysis proved the ferromagnetic nature in Fe3 O4 and superparamagnetic in Fe2 O3 .